PENINGKATAN KESEHATAN REPRODUKSI REMAJA MELALUI PENDAMPINGAN KELOMPOK TERAPEUTIK DI DESA INDROSARI, KECAMATAN BULUS PESANTREN, KEBUMEN - Rahmadhani, Wulan; Asti, Arnika Dwi (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2020)
Adolecent problem’s (aged >10 to 19 years) is a problem that needs to attentionsin national development in Indonesia. Adolescent health problems included physical, biological, mental dan social aspects. One effort to improved adolescent health was through Youth Care Health Service. To support for the success of program, it is necessary to established a youthclass where jointly discussing, exchanging opinions, exchanging experiences on the fulfilment of health and nutrition services, guided by the facilitator. Aimed  of this study was providing midwifery services in the form of counselling about coaching and mentoring adolescents in efforts to improve health.  Method in this study was used counselling/giving health knowledge and provided assistance through therapeutic communication to ten teenagers in the Indrosari, Bulus Pesantren, Kebumen. Result inthis study ware 9 students with excellent grades (90), 3 students with good grades (70). Results of mentoring in adolescent proups play a very important role as a forum for information for peers, especially in health care.